Characterisation of the induced pluripotent stem cell line NIMHi012-A derived from PBMCs of an epilepsy patient with a pathogenic variant in SCN1A gene - Madhura Milind Nimonkar; Ramya Sukrutha; Kenchaiah Raghavendra; Hansashree Padmanabha; Ghati K. Chetan; Bhupesh Mehta; Yogananda S. Markandeya; Gautham Arunachal (Stem Cell Research)
We report successful characterisation of the iPSC line NIMHi012-A, generated from the PBMCs of a patient with generalized epilepsy with febrile seizures plus (GEFS+). The mycoplasma-free cells expressed pluripotency markers, showed trilineage differentiation potential and had a normal karyotype. This cell line will serve as a platform to investigate the disease mechanism and develop novel patient-specific therapeutic strategies.